The Relationship Between Stunting and Anemia in Toddlers in Malaka Coastal Area, North Lombok - Danianto, Ario; Cholidah, Rifana; Amalia, Emmy; Purnaning, Dyah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Stunting is a major chronic nutritional problem with a high prevalence in Indonesia. This issue is crucial as it affects the quality of Indonesia's human resources in the future. One of the consequences of stunting is the increased incidence of anemia in toddlers. Anemia occurring early in life disrupts physical growth and leads to growth retardation. The relationship between anemia and stunting is an overlapping influence stemming from various levels. Efforts to prevent and reduce the rates of stunting and anemia must involve all parties comprehensively. Anemia in toddlers is a global health problem, both in terms of severity and prevalence. Globally, 1.6 million people are affected by anemia, and 47.4% of them are preschool-aged children. This study aims to determine the relationship between the occurrence of stunting and anemia in toddlers. The research was conducted through an analytical observational survey with a cross-sectional design. In this study, in the normal toddler group, of 26 samples, 25 children (96.15%) had normal Hb levels, and 1 child had mild anemia (3.85%). Meanwhile, in the 30 stunted toddlers, all samples had normal Hb levels (100%). The average Hb level in normal toddlers was 12.82 mg/dl, and in stunted toddlers, it was 12.81 mg/dl. No significant difference was found between the Hb levels of normal and stunted toddlers, with a p-value of 0.977 (p > 0.05).